Origin and impact of the oldest metazoan bioclastic sediments - Warren, L. V.; Simões, M. G. [UNESP]; Fairchild, T. R.; Riccomini, C.; Gaucher, C.; Anelli, L. E.; Freitas, B. T.; Boggiani, P. C.; Quaglio, F. (Geological Society of America, 2013)
The emergence of soft-bodied metazoans and the radiation of the earliest skeletal organisms substantially changed the ecological dynamics of Ediacaran environments, leading to the genesis of biogenic hard-part deposits for the fi rst time in Earth's history. The impact of bioclast origin on sedimentary processes is analyzed herein, focusing on the sedimentology and taphonomy of shell concentrations dominated by the Ediacaran index fossil Cloudina from the Itapucumí Group, Paraguay. Skeletal concentrations include both dense accumulations of parautochthonous, disarticulated specimens (Type 1 deposits) and in situ specimens preserved as loosely packed assemblages (Type 2 deposits). At that time, Cloudina was the critical source of durable biomineralized hard parts in an environment nearly free of other bioclasts. The simple fabric and geometry of these accumulations are typical of Cambrian-style shell beds. Despite their Precambrian age, these deposits indicate that the establishment of the Phanerozoic style of marine substrates and preservation in early shell beds was determined more by the acquisition of hard parts than by environmental changes. © 2013 Geological Society of America.
Keywords: Bioclastic sediments; Ecological dynamics; Ediacaran; Environmental change; Hard part; Precambrian; Sedimentary process; Taphonomy; Deposits; Sedimentology; bioclastic sediment; biomineralization; environmental change; metazoan; sedimentology; shell; skeleton; taphonomy; Paraguay; Cloudina; Metazoa